Analisis Kinerja Keuangan Perusahaan Manufaktur Tercatat di BEI Sebelum dan Selama Pandemi Covid-19 - Cindy Anindya Damayanti; Merawati, Endang Etty; Nelyumna (FEB-UP Press, 2024)
The objective of this research is to evaluate potential changes in the profitability, liquidity, and solvency ratios during the pre-Covid-19 period compared to the Covid-19 period. Only the firms in the food and beverage sectorthat are currently listed on the IDX will be taken into account for inclusion in this study. The phrase